Comparison of single- and double-spaced feeders with regard to damaging behavior in pigs - D'Alessio, Roberta Maria; Hanlon, Alison; O'Driscoll, Keelin (Frontiers in Veterinary Science, 2023)
This work compared the behaviour and performance of 24 groups of 12 pigs kept in pens with either a DOUBLE (one feed space aligned with the front wall of the pen (WALL), and one immediately adjacent (IN)) or SINGLE (WALL only) spaced feeder, from weaning until slaughter. Pens were equipped with a rack of fresh grass and a rubber toy (weaning phase) or a wooden board (finishing phase). Every 2 weeks, interaction with the enrichment, aggressive, harmful, and play behaviours were recorded for 5 minutes, 4 times a day. In addition, pigs were individually assessed every 2 weeks for ear, tail and flank injuries using a 4-point scale. Duration of feeder occupancy, feed-space occupancy, number of and duration of feeding bouts and aggressive behaviour at the feeder were recorded continuously from video recordings (twice while in the weaner stage and twice while in the finisher stage, 1 camera/pen; 1 h per occasion). Individual body weight was recorded at weaning, transfer and slaughter, and feed delivery was recorded daily at pen level; from these measurements, average daily gain, feed intake and feed conversion ratio were calculated. Data were analysed using SAS v9.4. There was no effect of treatment on damaging behaviours. Pigs in DOUBLE had worse tail lesion scores on 6 of the 9 recording days (P<0.001), but values rarely exceeded 1. Total feeder occupancy tended to be longer in DOUBLE than SINGLE (P=0.06). DOUBLE selected the IN feed space more often than WALL regarding the number of feeding bouts (P<0.001). During feeding, pigs in DOUBLE received fewer aggressive behaviours than SINGLE (P<0.001) and experienced fewer displacements than in SINGLE (P<0.001). Although both experimental groups had a similar weight at slaughter (P>0.05), FCR was lower in DOUBLE than SINGLE (P<0.05). These data suggest that doubling space at the feeder to two spaces/12 pigs reduced aggression and displacement behaviours at the feeder, indicating less competition for food. However, increasing feeder space was not a management strategy that could ensure reduced tail biting on commercial pig farms.